An examination of value and growth based investment strategies in the Australian equities market : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Finance at Massey University - Urquhart, Robert (Massey University, 2000)
Numerous studies have found that value-based investment strategies yield higher returns than growth-based investment strategies. However, controversy surrounds the interpretation of why value-based yield the higher returns. There is not consensus among researchers as to whether value stocks are fundamentally riskier than growth stocks, or whether psychological biases of investors result in an irrational pricing of stocks, and higher returns to the value stock portfolios. To add to the evidence of this debate, this thesis examines value, and growth-based investment strategies in the Australian equities market from 1990 to 2000. Value portfolios are formed by selecting stocks that have a strong past financial performance, and are expected to have a relatively poor future financial performance as gauged by financial variables. Growth portfolios are formed by selecting stocks that have a poor past financial performance, and are expected to have a relatively strong future financial performance as measured by financial variables. The financial variables used to classify stocks into the growth and value stock portfolios are the earnings-to-price, cash flow-to-price, book-to-market, and growth in sales variables. Examining one and two-year buy-and-hold returns, value stock portfolios are on average, found to yield higher returns than growth stock portfolios. The superiority of the value portfolio returns are also found to be invariant to the monthly calendar initiation date of the investment strategies. As far as an interpretation of the discrepancy in value and growth stock portfolio returns goes, the Capital Asset pricing Model (CAPM) measure of risk, β, is found to be misspecified. It is however, not clear whether the superior value portfolio returns are a consequence of investor irrationality, or value stock investments being riskier than growth stock investments. It seems as if the industry classification may be responsible for growth and value portfolio returns, and this may have an impact on the interpretation of the relationships between financial variables and stock returns. To interpret the relationships between the financial variables and stock returns, a multivariate linear regression model is applied to stock returns. Multicollinearity between the earnings-to-price and cash flow-to-price ratios is found, and when controlled for, the book-to-market variable is the only variable that is linearly related to stock returns.
Keywords: Australia; Investments; Stocks